Meta-Analysis: The Effect of PBL Learning Model on High School Students' Mathematical Critical Thinking Skills - Maleakhi Maleakhi (JURNAL PENDIDIKAN MATEMATIKA, 2026)
In Indonesia, mathematical critical thinking is a skill that students often lack and therefore needs attention. This study aims to analyze the effectiveness of implementing the PBL model on students’ mathematical critical thinking skills at the senior high school level, overall and by study characteristics such as sample size, region, and year of study, using a meta-analysis. A total of 13 primary studies that met the criteria were analyzed using a random-effects model in Comprehensive Meta-Analysis software. The results show that the combined effect size obtained is 1.011, which falls into the very large effect category, indicating that the PBL model has a positive and significant effect compared to conventional learning. In the analysis of study characteristics by effect size category, the group that conducted learning online during the COVID-19 pandemic had an effect size in the moderate category. In contrast, all other groups produced effect sizes in the very large category. Meanwhile, the heterogeneity test showed no significant differences in effect sizes across groups for the three study characteristics. These findings confirm that the PBL model is effective in improving students’ mathematical critical thinking skills at the senior high school level, but tends to be less effective when learning is conducted online. The implications of this study provide recommendations for teachers to optimize the implementation of PBL in the mathematics learning process and to consider its use across various situations and conditions. Keywords: Mathematical Critical Thinking Skills, Problem-Based Learning, High School Students, Meta-Analysis.